Penile Glans Amputation following Circumcision: A Case Report of a Rare Complication - Salman Soltani; Mahdi Mottaghi; Amir Jafarpisheh; Mahmoud Tavakkoli (Case Reports in Urology)
Circumcision is the most prevalent surgery among men. Like any other surgical intervention, it is associated with several complications. A rare shocking complication is glans amputation which is a urologic emergency. Herein, we present a 4-year-old boy with penile glans amputation following circumcision. The reimplantation was performed in less than two hours. We approximated the ends over a size 4 : 0 catheter. The urethral anastomosis was performed via 6 : 0 Vicryl sutures. Then, we sutured amputated glans in place via Vicryl 4 : 0. We immobilized the penis for a week via bandages used in penile reconstruction surgeries. We also used pentoxifylline to treat glans ischemia after surgery. The patient and his parents did not mention any difficulties or abnormalities while voiding, and the cosmetic result was favorable after three months of follow-up.